Alloy catalyst and preparation method and application thereof

By preparing nanospray uniformly dispersed alloy catalysts, the problems of low H2O2 preparation reaction rate and poor electron selectivity in the prior art are solved, and efficient hydrogen peroxide production is achieved.

CN119663358APending Publication Date: 2025-03-21SHANGHAI ELECTRICGROUP CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411883352.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, the reaction rate or electron selectivity is low when preparing H2O2, making it difficult to meet the efficient and safe H2O2 production needs.

Method used

An alloy catalyst is used to carry the carbon nanotubes and noble metal precursors on the foam nickel. By adjusting the pH value and reaction conditions, an alloy catalyst with uniform dispersion of nanospray is prepared.

Benefits of technology

It improves the selectivity and reactivity of the two electrons, significantly improves the output efficiency of hydrogen peroxide, and performs better than traditional single catalysts or carbon oxide nanotube catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663358A_ABST
    Figure CN119663358A_ABST
Patent Text Reader

Abstract

The invention discloses an alloy catalyst as well as a preparation method and application thereof. The preparation method mainly comprises the following steps: loading a mixture containing a carbon nanotube and a noble metal precursor A on foamed nickel to prepare an electrode material; adding the electrode material into a precious metal precursor B solution, adjusting the pH value to 6.5-7.5, and carrying out a reaction to prepare an alloy catalyst; wherein the noble metal in the noble metal precursor A is Pt and / or Pd; the noble metal in the noble metal precursor B is one or more of Au, Ag and Hg. The alloy catalyst provided by the invention can enhance two-electron selectivity, nano spray is uniformly dispersed, and hydrogen peroxide is easy to prepare. Compared with a traditional single catalyst or an oxidized carbon nanotube catalyst, the alloy catalyst has the advantages that the reaction activity and selectivity are improved, and the output efficiency of hydrogen peroxide is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an alloy catalyst and a preparation method and application thereof. Background Art

[0002] H 2 O 2 As a green and environmentally friendly multifunctional oxidant, it occupies an extremely important position in the modern chemical industry. In recent years, with the increasing demand for H 2 O 2 The increasing market demand has made it one of the most important chemical products in the world. 2 O 2 The industrial production of anthraquinone mainly relies on the energy-intensive indirect anthraquinone redox process. However, this traditional process has the problems of high energy consumption and serious pollution, and requires the use of large equipment and expensive catalysts, which makes it difficult to meet the needs of green and sustainable development.

[0003] Although the use of hydrogen (H 2 ) and oxygen (O 2 ) as raw materials in atom economy and H 2 O 2 Distributed production has advantages, but due to the presence of H 2 O 2 The low yield and the risk of explosion hinder the large-scale application of this technology. Therefore, it is necessary to develop an efficient and safe H 2 O 2 The production process has important research significance.

[0004] In recent years, the electrochemical two-electron oxygen reduction pathway has been used to achieve H 2 O 2 The continuous decentralized production of H 2 O 2 It solves the storage and transportation problems of renewable energy and realizes the efficient use of renewable energy. It is considered to be a promising H 2 O 2 Preparation process.

[0005] The ORR reaction involves a multi-electron transfer process, mainly through the two-electron pathway (2e - ORR) generates H 2 O 2 or through four electrons (4e - In the prior art, single noble metal catalysts have been shown to have 2e - ORR performance, but these metals (such as Au, Ag or Hg) have poor 2The binding effect is weaker, showing a lower reaction rate and higher overpotential in the reaction. 2 Metals with stronger interactions (such as Pt and Pd) are more likely to use a four-electron pathway, thus limiting the H 2 O 2 Selective generation. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the existing technology of preparing H 2 O 2 In order to overcome the defects of low reaction rate or poor electron selectivity, an alloy catalyst and its preparation method and application are provided. The alloy catalyst provided by the present invention can enhance the two-electron selectivity, the nano-spray is evenly dispersed, and hydrogen peroxide is easy to prepare. Compared with the traditional single catalyst or oxidized carbon nanotube catalyst, the alloy catalyst of the present invention improves the reaction activity and selectivity, and greatly improves the output efficiency of hydrogen peroxide.

[0007] The present invention solves the above technical problems through the following technical solutions.

[0008] The present invention also provides a method for preparing an alloy catalyst, which mainly comprises the following steps: loading a mixture containing carbon nanotubes and a noble metal precursor A on nickel foam to obtain an electrode material; adding the electrode material to a solution of a noble metal precursor B, adjusting the pH value to 6.5-7.5, and reacting to obtain an alloy catalyst;

[0009] Wherein, the precious metal in the precious metal precursor A is Pt and / or Pd; the precious metal in the precious metal precursor B is one or more of Au, Ag and Hg.

[0010] In the present invention, the carbon nanotubes may be porous carbon nanotubes.

[0011] The porous carbon nanotubes can be prepared by the following steps: multi-walled carbon nanotubes react with nitric acid and then undergo carbonization treatment to obtain porous carbon nanotubes.

[0012] The mass volume ratio of the multi-walled carbon nanotubes to the nitric acid may be 1 g:(1800-2200) mL, for example, 1 g:2100 mL.

[0013] The temperature of the reaction may be 70-90°C, such as 80°C.

[0014] The reaction time may be 5-50 h, for example 24 h.

[0015] After the reaction and before the carbonization treatment, centrifugal washing and drying operations may also be performed.

[0016] The temperature of the carbonization treatment may be 700-900°C, for example 800°C.

[0017] The carbonization treatment time may be 4-8 hours, for example 6 hours.

[0018] In the present invention, the precious metal precursor A can be selected from one or more of chloroplatinic acid, chloroplatinous acid, potassium chloroplatinate, potassium chloroplatinite, sodium chloroplatinate, sodium chloroplatinite, ammonium chloroplatinate, ammonium chloroplatinite, palladium chloride, potassium chloropalladate, sodium chloropalladate, ammonium chloropalladate, potassium chloropalladate, sodium chloropalladate and ammonium chloropalladate, such as chloroplatinic acid or palladium dichloride.

[0019] In the present invention, the mass ratio of the carbon nanotubes to the noble metal precursor A may be (1-3):1, for example, 2:1.

[0020] In the present invention, the mixture may further include a solvent and Nafion.

[0021] The solvent may be conventional in the art, such as isopropanol.

[0022] The mass volume ratio of the carbon nanotubes to the solvent may be 1 mg:(0.1-0.3) mL, for example, 1 mg:0.2 mL.

[0023] The concentration of Nafion can be conventional in the art, such as 5%.

[0024] The mass volume ratio of the carbon nanotubes to the Nafion can be 1 mg:(5-10) μL, for example, 1 mg:6 μL or 1 mg:8 μL.

[0025] In the present invention, the mixture can be prepared by mixing raw materials and then dispersing them.

[0026] The dispersion rate may be 15-25 m / s, for example 20 m / s.

[0027] The dispersion time may be 150-250 s, for example 180 s.

[0028] In the present invention, the specifications of the nickel foam may be conventional in the art, such as 5 cm*5 cm.

[0029] In the present invention, the load may be applied by spraying.

[0030] In the present invention, the loading may be followed by a drying operation, and the drying temperature may be conventional in the art, such as 70°C.

[0031] In the present invention, in the noble metal precursor B solution, the noble metal precursor B can be selected from one or more of gold trichloride, chloroauric acid, sodium chloroaurate, potassium chloroaurate, ammonium chloroaurate, silver nitrate, silver chloride, silver fluoride, silver bromide, silver iodide, mercuric chloride, mercurous chloride, mercuric nitrate and mercuric acetate, such as chloroauric acid.

[0032] In the present invention, the noble metal precursor B solution may be an aqueous solution of the metal precursor B.

[0033] In the present invention, in the noble metal precursor B solution, the concentration of the noble metal precursor B may be 1-3 μg / mL, for example, 2 μg / mL or 2.4 μg / mL.

[0034] In the present invention, the mass ratio of the carbon nanotubes to the noble metal precursor B may be (100-150):1, such as 120:1 or 125:1.

[0035] In the present invention, the pH value is preferably 7.

[0036] In the present invention, the pH adjuster used may be an alkaline solution.

[0037] The alkaline solution may be a sodium hydroxide solution. The concentration of the sodium hydroxide solution may be conventional in the art, such as 1 mol / L.

[0038] In the present invention, the reaction time may be 1-3 hours, for example 2 hours.

[0039] In the present invention, the reaction may be followed by washing and drying operations.

[0040] The present invention also provides an alloy catalyst, which is prepared by the above preparation method.

[0041] The present invention also provides an alloy catalyst, which includes metal A, metal B, a carbon-based material and nickel foam; wherein the metal A is Pt and / or Pd, and the metal B is one or more of Au, Ag and Hg.

[0042] In the present invention, metal A and O 2 The interaction between metal B and O 2 The interaction is weak.

[0043] In the present invention, the metal A is preferably Pd.

[0044] In the present invention, the metal B is preferably Au.

[0045] The present invention also provides an application of the alloy catalyst as a cathode material in electrochemical preparation of hydrogen peroxide.

[0046] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0047] The reagents and raw materials used in the present invention are commercially available.

[0048] The positive and progressive effects of the present invention are:

[0049] The alloy catalyst provided by the present invention can enhance the two-electron selectivity, and the noble metal precursor is evenly dispersed on the carrier, which is convenient for the catalytic reaction of hydrogen peroxide. Compared with the traditional single catalyst or oxidized carbon nanotube catalyst, the alloy catalyst of the present invention improves the reaction activity and selectivity, and greatly improves the output efficiency of hydrogen peroxide. In some preferred embodiments, the noble metal precursor can be dispersed on the carrier in the form of nano spray, and the load is more uniform, which further improves the output efficiency of hydrogen peroxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 It is the standard curve of UV spectrophotometer and the method of calculating the concentration of hydrogen peroxide. DETAILED DESCRIPTION

[0051] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0052] Example 1

[0053] (1) Preparation of electrode materials

[0054] 0.2 g of multi-walled carbon nanotubes and 200 mL of nitric acid were added to a three-necked round-bottom glass flask, stirred and refluxed at 80 °C, oxidized for 24 h, the slurry was taken out, centrifuged, washed with water and ethanol until neutral, dried, and carbonized at high temperature 800 °C for 6 h to obtain oxidized porous nanotubes (porous carbon nanotubes).

[0055] Take 25 mg of oxidized porous nanotubes (porous carbon nanotubes) and 12.5 mg of palladium chloride and disperse them in 5 mL of isopropanol, add 200 μL of 5% Nafion, use Pre-max at 20 m / s, disperse for 180 s. Spray the dispersed solution evenly on a 5 cm * 5 cm nickel foam with a spray gun and dry at 70 °C.

[0056] (2) Catalyst material deposition

[0057] 0.2 mg HAuCl 4 ·3H 2O was added to 100 mL of deionized water, and then the sprayed nickel foam carrier was added. 1 mol / L sodium hydroxide solution was added dropwise to the above solution until the pH was 7. After the addition was completed, the reaction was stirred for 2 h. Subsequently, the solid precipitate was filtered and washed with 50 mL of deionized water. The solid was dried under vacuum at room temperature overnight to obtain an alloy catalyst.

[0058] Comparative Example 1

[0059] 0.2 g of multi-walled carbon nanotubes and 200 mL of nitric acid were added to a three-necked round-bottom glass flask, stirred and refluxed at 80 °C, oxidized for 12 h, the slurry was taken out, centrifuged, washed with water and ethanol until neutral, dried, and carbonized at high temperature 800 °C for 6 h to obtain oxidized porous nanotubes (porous carbon nanotubes).

[0060] Take 25 mg of oxidized porous nanotubes (porous carbon nanotubes), disperse them in 5 mL of isopropanol, add 200 μL of 5% Nafion, use Pre-max at 10 m / s, disperse for 180 s. Spray the dispersed solution evenly on a 5 cm * 5 cm nickel foam with a spray gun, and dry at 70 °C to obtain an alloy catalyst.

[0061] Comparative Example 2

[0062] 0.2 g of multi-walled carbon nanotubes and 200 mL of nitric acid were added to a three-necked round-bottom glass flask, stirred and refluxed at 80 °C, oxidized for 48 h, the slurry was taken out, centrifuged, washed with water and ethanol until neutral, dried, and carbonized at high temperature 800 °C for 6 h to obtain oxidized porous nanotubes (porous carbon nanotubes).

[0063] Take 25 mg of oxidized porous nanotubes (porous carbon nanotubes) and 12.5 mg of palladium chloride and disperse them in 5 mL of isopropanol. Add 200 μL of 5% Nafion and use Pre-max at 15 m / s for 180 seconds. Spray the dispersed solution evenly on a 5 cm * 5 cm nickel foam with a spray gun and dry at 70 °C to obtain an alloy catalyst.

[0064] Effect Example

[0065] The alloy catalysts prepared in the above examples and comparative examples were used as cathode catalyst layers, and a 5 cm*5 cm commercial catalyst (purchased from Tanaka, model 10E50E) was used as an anode to assemble an electrolytic cell.

[0066] Preparation and detection of hydrogen peroxide: 250 mL 6 M KOH was placed in the anode chamber of the electrolytic cell, 250 mL 2 M KOH was placed in the cathode chamber, air was passed through the cathode side, and the circulation pump was turned on to input the electrolyte solution into the anode and cathode chambers at a pump rate of 70 mL / min to fill the chambers. The test potential range was 1-1.7 V. After electrolysis for 1 h, 1 mL of sample was taken for UV analysis.

[0067] Preparation of standard curve: Using titanium salt photometry, hydrogen peroxide and Ti 4+ The reaction generates a yellow precipitate of peroxide-titanium complex, which can be dissolved by sulfuric acid and detected by a UV spectrophotometer at around 395 nm. The color depth of the solution is proportional to the hydrogen peroxide content. Plot a standard curve and insert the measured absorbance into the standard curve to obtain the concentration of hydrogen peroxide produced.

[0068] The results are shown in the following table.

[0069] Table 1

[0070]

[0071] Compared with Example 1, Comparative Example 1 does not contain precious metals, while Comparative Example 2 only contains 2 Noble metals with strong interactions with O 2 According to the comparison, the present invention produces the highest concentration of hydrogen peroxide.

Claims

1. A method for preparing an alloy catalyst, characterized in that: The method mainly comprises the following steps: loading a mixture containing carbon nanotubes and a noble metal precursor A on nickel foam to obtain an electrode material; adding the electrode material into a solution of a noble metal precursor B, adjusting the pH value to 6.5-7.5, reacting, and obtaining an alloy catalyst; Wherein, the precious metal in the precious metal precursor A is Pt and / or Pd; the precious metal in the precious metal precursor B is one or more of Au, Ag and Hg.

2. The method for preparing the alloy catalyst according to claim 1, characterized in that: The carbon nanotubes are porous carbon nanotubes; and / or, the noble metal precursor A is selected from one or more of chloroplatinic acid, chloroplatinous acid, potassium chloroplatinate, potassium chloroplatinite, sodium chloroplatinate, sodium chloroplatinite, ammonium chloroplatinate, ammonium chloroplatinite, palladium chloride, potassium chloropalladate, sodium chloropalladate, ammonium chloropalladate, potassium chloropalladate, sodium chloropalladate and ammonium chloropalladate, such as chloroplatinic acid or palladium dichloride; And / or, the mass ratio of the carbon nanotubes to the noble metal precursor A is (1-3):1, for example, 2:1; And / or, the mixture further comprises a solvent and Nafion.

3. The method for preparing the alloy catalyst according to claim 2, characterized in that: The porous carbon nanotubes are prepared by the following steps: multi-walled carbon nanotubes react with nitric acid and then perform carbonization treatment to obtain porous carbon nanotubes; Wherein, the mass volume ratio of the multi-walled carbon nanotubes and the nitric acid is preferably 1g:(1800-2200)mL; the reaction temperature is preferably 70-90°C; the reaction time is preferably 5-50h; the carbonization temperature is preferably 700-900°C; the carbonization time is preferably 4-8h; And / or, the solvent is isopropanol; and / or, the mass volume ratio of the carbon nanotubes to the solvent is 1 mg:(0.1-0.3) mL; And / or, the mass volume ratio of the carbon nanotubes to the Nafion is 1 mg:(5-10) μL.

4. The method for preparing the alloy catalyst according to claim 1, characterized in that: The mixture is prepared by mixing the raw materials and then dispersing them; the dispersing rate is preferably 15-25 m / s; and the dispersing time is preferably 150-250 s; and / or, the load is applied by spraying; And / or, the loading may further include a drying operation.

5. The method for preparing the alloy catalyst according to claim 1, characterized in that: In the noble metal precursor B solution, the noble metal precursor B is selected from one or more of gold trichloride, chloroauric acid, sodium chloroaurate, potassium chloroaurate, ammonium chloroaurate, silver nitrate, silver chloride, silver fluoride, silver bromide, silver iodide, mercuric chloride, mercurous chloride, mercuric nitrate and mercuric acetate, such as chloroauric acid; And / or, the noble metal precursor B solution is an aqueous solution of metal precursor B; and / or, in the noble metal precursor B solution, the concentration of the noble metal precursor B is 1-3 μg / mL, for example, 2 μg / mL or 2.4 μg / mL; And / or, the mass ratio of the carbon nanotubes to the noble metal precursor B is (100-150):1, for example, 120:1 or 125:

1.

6. The method for preparing the alloy catalyst according to claim 1, characterized in that: The pH value is 7; And / or, the pH adjusting agent used is an alkaline solution; the alkaline solution is preferably a sodium hydroxide solution; And / or, the reaction time is 1-3h.

7. An alloy catalyst, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 6.

8. An alloy catalyst, characterized in that The invention comprises metal A, metal B, carbon-based material and nickel foam; wherein the metal A is Pt and / or Pd, and the metal B is one or more of Au, Ag and Hg.

9. The alloy catalyst according to claim 8, characterized in that The metal A is Pd; And / or, the metal B is Au.

10. Use of the alloy catalyst according to any one of claims 7 to 9 as a cathode material in electrochemical preparation of hydrogen peroxide.